MOMORDICA CHARANTIA L. (PARE) SEBAGAI AGEN HIPOGLIKEMIK DALAM MANAJEMEN DIABETES MELITUS TIPE 2 - William, Jessica Audrey; Ananta, Vito; Adiputra, Ricky Fajar; Adenina, Syarinta (Bahasa Indonesia, 2025)
Background: Diabetes Mellitus is a condition characterized by consistently high blood glucose levels due to a chronic metabolic disorder. Type 2 diabetes mellitus accounts for 90% of all cases. According to the 10th edition of the International Diabetes Federation report, Indonesia ranks fifth in the world for the number of type 2 diabetes patients, with 19.5 million affected individuals. Efforts to address the rise in type 2 diabetes cases require effective management to maintain normal blood glucose levels. Currently, oral hypoglycemic drugs are the preferred treatment for type 2 diabetes. However, potential side effects can raise concerns among patients. As a result, alternative approaches, such as herbal therapy, may help reduce the prevalence of type 2 diabetes. Momordica charantia L. is known for its hypoglycemic properties. Methods: The literature search is conducted in PubMed, ScienceDirect, and ClinicalKey databases. The articles used were those published in the last 10 years, and the keywords included "type 2 diabetes," "Momordica charantia L.," "bitter melon," and "blood glucose." Results: Momordica charantia L. contains many compounds with antidiabetic properties. These compounds include polysaccharides, peptides, terpenoids, saponins, alkaloids, flavonoids, and others. Momordica charantia L. contains the insulin-mimetic compound mclRBP-19, which is associated with a decrease in FBG and HbA1c levels. Triterpenoids have been found to stimulate GLUT-4 translocation in muscle and fat cells, as well as inhibit PTP1B activity. Additionally, charantin is known to inhibit DPP4 activity. Conclusion: Momordica charantia L. has the potential to lower blood glucose levels in type 2 diabetes patients through its bioactive components.